2009
DOI: 10.1038/clpt.2009.69
|View full text |Cite
|
Sign up to set email alerts
|

The Value, Qualification, and Regulatory Use of Surrogate End Points in Drug Development

Abstract: The acceptance and use of either surrogate end points (SEPs) or efficient clinical end points are associated with greater and more rapid availability of new medicines as compared with disease situations for which clinical end points are inefficient or no surrogates exist. This review of the history of the development, qualification, and acceptance of key SEPs shows that both successes and failures had three key characteristics: (i) apparent biologic plausibility, (ii) prognostic value for the outcome of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 45 publications
1
51
0
1
Order By: Relevance
“…44 44 These estimates support informal arguments made by the cancer research community; see, for example, Korn and Stanski (2005), US Institute of Medicine (2008), Lathia et al (2009), and American Society for Clinical Oncology (2011). In the case of cardiovascular disease, the set of surrogate endpoints accepted by the US FDA were initially identified by the Framingham Heart Study, a large-scale, multi-decade, federally-funded observational study which identified factors such as high blood pressure as risk factors.…”
Section: Discussionsupporting
confidence: 57%
“…44 44 These estimates support informal arguments made by the cancer research community; see, for example, Korn and Stanski (2005), US Institute of Medicine (2008), Lathia et al (2009), and American Society for Clinical Oncology (2011). In the case of cardiovascular disease, the set of surrogate endpoints accepted by the US FDA were initially identified by the Framingham Heart Study, a large-scale, multi-decade, federally-funded observational study which identified factors such as high blood pressure as risk factors.…”
Section: Discussionsupporting
confidence: 57%
“…Research reported in this publication was supported by the National Institute on Aging and the NIH Common Fund, 52 See, for example, the discussion in Cutler and Kadiyala (2003). 53 This type of argument has also been made informally by the cancer research community; see, for example, Korn and Stanski (2005), US Institute of Medicine (2008), Lathia et al (2009), and American Society for Clinical Oncology (2011). Collins (2012) provides an example of a technology -a chip that mimics how humans respond to a drug -that could serve the same role as a surrogate endpoint, by identifying promising candidate drugs more quickly.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Subsequent clinical trials helped to validate these prognostic factors, which led the FDA to accept them as surrogate endpoints in cardiovascular trials (Meyskens et al 2011). Researchers have argued that without these surrogate endpoints, it is unclear whether drugs such as betablockers, ACE-inhibitors, and statins would have reached the market as treatments for heart disease (Lathia et al 2009;Meyskens et al 2011). Note that public subsidies -such as federal support for the Framingham study -were likely important in this context, because any individual firm's investment in discovering and validating surrogate endpoints would generate benefits that largely spill over to other firms.…”
Section: Budish Et Al Page 31mentioning
confidence: 99%
“…La valeur du biomarqueur comme outil décisionnel doit par ailleurs être périodiquement réévaluée à la lumière de tous les travaux disponibles comme l'a bien montré l'historique dans d'autres domaines thérapeutiques (densité minérale osseuse pour l'ostéoporose, extra systoles ventriculaires et prévention de l'infarctus du myocarde, etc.). [2] 3. Quels biomarqueurs pour la maladie d'Alzheimer…”
Section: Disease-modifiers : Cours éVolutif Et Effet Physiopathologiqueunclassified